Kindia (Pavetteae, Rubiaceae), a new cliff-dwelling genus with chemically profiled colleter exudate from Mt Gangan, Republic of Guinea - Martin Cheek; Sékou Magassouba; Melanie-Jayne R. Howes; Tokpa Doré; Saïdou Doumbouya; Denise Molmou; Aurélie Grall; Charlotte Couch; Isabel Larridon (PeerJ, 2018)
A new genus Kindia (Pavetteae, Rubiaceae) is described with a single species, Kindia gangan, based on collections made in 2016 during botanical exploration of Mt Gangan, Kindia, Republic of Guinea in West Africa. The Mt Gangan area is known for its many endemic species including the only native non-neotropical Bromeliaceae Pitcairnia feliciana. Kindia is the fourth endemic vascular plant genus to be described from Guinea. Based on chloroplast sequence data, the genus is part of Clade II of tribe Pavetteae. In this clade, it is sister to Leptactina sensu lato (including Coleactina and Dictyandra). K. gangan is distinguished from Leptactina s.l. by the combination of the following characters: its epilithic habit; several-flowered axillary inflorescences; distinct calyx tube as long as the lobes; a infundibular-campanulate corolla tube with narrow proximal section widening abruptly to the broad distal section; presence of a dense hair band near base of the corolla tube; anthers and style deeply included, reaching about mid-height of the corolla tube; anthers lacking connective appendages and with sub-basal insertion; pollen type 1; pollen presenter (style head) winged and glabrous (smooth and usually hairy in Leptactina); orange colleters producing a vivid red exudate, which encircle the hypanthium, and occur inside the calyx and stipules. Kindia is a subshrub that appears restricted to bare, vertical rock faces of sandstone. Fruit dispersal and pollination by bats is postulated. Here, it is assessed as Endangered EN D1 using the 2012 IUCN standard. High resolution LC-MS/MS analysis revealed over 40 triterpenoid compounds in the colleter exudate, including those assigned to the cycloartane class. Triterpenoids are of interest for their diverse chemical structures, varied biological activities, and potential therapeutic value.